A Model for Paleoamerican Coastal Zone Preference for the Atlantic Slope of Eastern North America Since the Last Glacial Maximum. (2nd October 2017) - Sain, Douglas A.
ABSTRACT: Paleoamerican colonization models have emphasized the importance of coastal zones for provisioning hunter gatherers with a diverse range of subsistence resources. This article expands on recent research by Lowery et al. 2012, and presents a model to explain the distribution of Clovis points across the Atlantic slope of Eastern North America. Marine transgression since the last glaciation has submerged large tracts of the Atlantic continental shelf. Global bathymetric data was used to estimate the Clovis age shoreline from Delaware to Florida. Clovis biface data for modern coastal areas, obtained from the Paleoindian database of the Americas, was compared to the slope of the paleo-shoreline to predict coastal zone preference. Results indicate a relationship between point distribution and coastal zone type. Areas where major rivers with high-quality tool-stone intersect broad coastal zones served important roles to Clovis subsistence adaptations. The potential exists for early Paleoamerican sites along the continental shelf submerged beneath 55–75 m of the Atlantic Ocean. Modern coastal regions with high densities of Clovis points may serve as analogues for identifying earlier sites that have been submerged as a result of marine transgression.